2021
DOI: 10.3389/fenvs.2021.633875
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage Among Sea Transport, Trade Liberalization and Industrial Development in the Context of CO2: An Empirical Investigation From China

Abstract: The major goal of this paper is to focus on the linkage between sea transportation, trade liberalization and industrial development in the context of carbon dioxide emission. With this respect, it is attempted to analyze the effects of independent variables on the dependent variable carbon dioxide emission for China by using annual data ranging from 1960 to 2019 with the help of econometric methods such as fully modified least square, dynamic ordinary least square, canonical co-integrating regression, autoregr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…However; in this part of the article, primarily the series that consider the relationship among economic growth, energy consumption, air transportation and CO 2 emissions are discussed as well. Some of these research paper investigate the CO 2 emissions, energy consumption, and economic growth by taking into account the Environmental Kuznets Curve (EKC) in the academic literature (Beşe and Kalayci, 2021;Farooq et al, 2022, Kalayci andÖzden, 2021;Ozkan et al, 2019;Ozturk et al, 2016;Ozturk et al, 2021;Sheikhzeinoddin et al, 2022;Yazici, 2022). Considering the air transportation as independent variable in terms of EKC hypothesis, there are limited amount researches (Erdoğan et al, 2020;Gyamfi et al, 2022;Kalayci and Yanginlar, 2016;Kalayci and Yazici, 2016) in the academic literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However; in this part of the article, primarily the series that consider the relationship among economic growth, energy consumption, air transportation and CO 2 emissions are discussed as well. Some of these research paper investigate the CO 2 emissions, energy consumption, and economic growth by taking into account the Environmental Kuznets Curve (EKC) in the academic literature (Beşe and Kalayci, 2021;Farooq et al, 2022, Kalayci andÖzden, 2021;Ozkan et al, 2019;Ozturk et al, 2016;Ozturk et al, 2021;Sheikhzeinoddin et al, 2022;Yazici, 2022). Considering the air transportation as independent variable in terms of EKC hypothesis, there are limited amount researches (Erdoğan et al, 2020;Gyamfi et al, 2022;Kalayci and Yanginlar, 2016;Kalayci and Yazici, 2016) in the academic literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are kinds of research in the academic literature examining the nexus between CO 2 emissions, air transportation and GDP. Some of these manuscript investigate the carbon emissions and economic growth theory known as Environmental Kuznets Curve (EKC) in the academic literature (Beşe and Kalayci, 2021;Dursun, 2022;Egilmez, 2020;Güdül, 2021;Kalayci and Özden, 2021; Kalayci and Yazici, 2016;Özkan et al, 2019;Öztürk et al, 2016;Öztürk et al, 2021;Sarkodie and Öztürk, 2020;Sumaira and Siddique, 2022;Tarazkar et al, 2021;Yazici, 2022). The major goal of this manuscript is to examine the stable long-run nexus among energy consumption, economic growth, civil aviation, and CO 2 emissions by performing the ARDL, DOLS and panel data analysis for Baltic countries from 1992 to 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A remarkable part of academic literature has investigated various features of the effect of civil aviation on environmental pollution. In this sense, recent academic research regarding the relationship between air transport, economic growth, and environmental pollution (Eğilmez, 2020;Erdogan et al, 2020;Gyamfi et al, 2022;Kalayci and Özden, 2021;Kalayci and Yazici 2016;Ozkan et al, 2019;Ozturk et al, 2021;Sohail et al, 2021;Yazici, 2022) have suggested that reducing the existence of dirtiness is so vital in terms of protecting the environment which is mostly depend on the government policies and economic sanctions. Altuntaş and Kılıç (2021) investigate the relationship between total airline passenger, freight traffic and Gross Domestic Product (GDP) for Turkey by implementing ARDL and Toda Yamamoto methods.…”
Section: Literature Reviewmentioning
confidence: 99%